The nervous system of the neotropical millipede Gymnostreptus olivaceus Schubart, 1944 (Spirostreptida, Spirostreptidae) shows an additional cell layer - Francisco, Annelise [UNESP]; Fontanetti, Carmem S.; Nocelli, Roberta C.F. [UNESP] (Brill Academic Publishers, 2015)
This study presents a morphological description of the central nervous system of the neotropical millipede Gymnostreptus olivaceus and the first report of an outer cell layer surrounding the nervous system in Diplopoda the nervous system of this species consists of a brain formed by the fusion of proto-, deuto-And tritocerebrum, as well as a ventral nerve cord with metamerically arranged ganglia that extends through the entire length of the animal's body the optic lobes, mushroom bodies and olfactory glomeruli of this species were located and described. As has been reported for other millipedes, the nervous system of G. olivaceus comprises a cortical layer in which three types of neurons could be identified and an inner region of neuropil, both of which are wrapped and protected by a perineurium and a neural lamella. However, more externally to the neural lamella, there is a discontinuous and irregular outer cell sheath layer containing distinctive cells whose function appears to be linked to the nutrition and protection of neurons.
Keywords: Blood-nerve barrier; brain; diplopod; nerve cord